DEVELOPMENT OF MEDIA COMPETENCE OF FUTURE TEACHERS IN THE CONDITIONS OF DIGITAL EDUCATION - Uaidullakyzy, E.; Askarkyzy, S.; Жунусбекова, Азиза; Bekzhanova, B.; Tolegenov, B.O. (Pedagogy and Psychology, 2023)
The article presents an analysis of the development of media competence of future teachers in the context of digital education. The main aspect of the analysis is the ability to study the levels of development of media competence of future teachers, and analysis of the development of media competence of future teachers in the context of digital education. According to the goal of this study, an analysis of the psychological and pedagogical literature on the topic under study was carried out, as well as an analysis of the motivational component, which includes the motives for contact with media texts, the contact component as the frequency of communication with the media, informational, creative, perceptual, evaluative and practical components. When conducting an empirical study, modified blocks of questions of the A.V. Fedorov methodology were used to identify the development of media competence of future teachers. The relevance of the topic under study is also described. The definition of «media competence» is given and the analysis of foreign literature in this area is carried out. The levels of development of perceptual, interpretive, and creative indicators were identified. The relationship between perceptual and interpretive indicators, formed in the process of mutual analysis and evaluation of media resources, was noted. In the process of developing media competence, future teachers acquire important skills for professionals of the future: new media literacy, virtual collaboration, transdisciplinarity, and design thinking.